Un repaso de los conceptos sobre capacidad y esfuerzo fiscal, y su aplicación en los gobiernos locales mexicanos - Sour, Laura (El Colegio de México A.C., 2008)
This study reviews the methods used to calculate the fiscal effort and capacity of a region, showing that the lack of available information reduces the possibilities of examining these aspects of public finances. It also presents some of the theoretical and empirical efforts made to provide an overview of the issue. The fiscal effort and capacity of 2,412 local governments in Mexico is calculated for the period from 1993 to 2004. The results question the myth that large local governments tend to make a greater fiscal effort as a result of the policy of transfers, regardless of whether or not the latter are conditioned.